Health care resource use and costs associated with adult pneumococcal disease in the United States from 2017 to 2019, stratified by age and health risk: a retrospective cohort study - Cossrow, Nicole; Bailey, M. Doyinsola; Huang, Yi-Ling; Ai, Lei; Mohanty, Salini; McGuinn, Valina C.; Johnson, Kelly D. (Frontiers in Public Health, 2025)
BackgroundAdult pneumococcal disease (PD) represents a significant clinical and economic burden in the United States. Individuals with immunocompromising conditions and other chronic medical conditions, as well as those ≥65 years of age, have an increased risk of acute PD and its long-term complications. The aim of the current study was to describe the health care resource use and direct health care costs associated with invasive PD (IPD) and non-bacteremic pneumococcal pneumonia (NBPP) among adults in the United States, stratified by age group and health-based risk level.MethodsThis was a retrospective study of administrative claims from the Merative™ MarketScan® Commercial Database from 2017 to 2019. The study population comprised individuals ≥18 years of age with ≥1 episode of IPD (with hospitalization) or NBPP (with or without hospitalization) during the study period. The study outcomes were the PD-associated health care resource use (outpatient visits and length of any hospitalizations, in days) and direct health care costs per episode.ResultsThe average health care resource use and direct costs associated with PD were significantly higher for IPD (mean [95% CI] overall cost 49,481 [45,803–53,159] per episode; N = 949 affected individuals) than for NBPP with hospitalization (27,330 [23,807–30,852] per episode; N = 389) and NBPP without hospitalization (1,090 [927–1,252] per episode; N = 1,951). For IPD and for NBPP without hospitalization, the direct costs of treatment were significantly higher among groups with immunocompromising or other relevant comorbidities. The costs associated with NBPP without hospitalization were also significantly higher in the oldest age group (≥65 years).ConclusionTargeting PD prevention efforts to high-risk groups based on age and/or health risk level could decrease the clinical and economic burden of adult PD in the US.